Pengaruh Sosialisasi Self-Declare Terhadap Keputusan Sertifikasi Halal pada Pelaku UMKM Kota Tasikmalaya - Ikhwan, Muhammad; Nandang, Nandang; Rachmani, Nizza Nadya (Economic Reviews Journal, 2025)
This study aims to analyze the influence of self-declare socialization on the decision of micro, small, and medium enterprises (MSMEs) in Tasikmalaya City to obtain halal certification. The research employs a quantitative approach with a descriptive and verification design. The study population consists of MSMEs that meet the self-declare requirements, with a sample of 100 respondents selected using the convenience sampling technique. Data were collected through a Likert scale questionnaire and analyzed using validity testing, reliability testing, descriptive analysis, classical assumption testing, and simple linear regression. The results indicate that self-declare socialization has a positive and significant effect on halal certification decisions, with a positive regression coefficient and a significance level of 0.000 < 0.05. The coefficient of determination (R²) of 0.670 shows that 67% of the variation in halal certification decisions can be explained by self-declare socialization, while the remaining 33% is influenced by other factors such as understanding, halal awareness, and perception. These findings suggest that the more effective the self-declare socialization, the greater the likelihood that MSMEs will decide to pursue halal certification.